Reducing Anemia in Pregnant Women through a Community-Based Intervention - Elías Peñafiel, Lourdes (1998)
OBJECTIVE : To evaluate the impact of a preventive - emotional intervention, based on the community to improve knowledge and iron intake of pregnant women with anemia. METHODS : The study was conducted in marginal urban areas of the Southern Cone of Lima - Peru , 76 anemic women were surveyed in the 2nd trimester, predominantly young (50 %, 17% adolescents). The intervention was characterized by the participation of organized women in the promotion of women's health through supplementation and monitoring of iron intake through the knowledge of the sociocultural profile of anemic pregnant and carrying out an intervention in information, Education and Communication (IEC ) . RESULTS : A high percentage of women with a history of abortion ( 23%). Just over half (51 % ) of mothers were reported by health promoters Usability iron intake . Recovered from anemia 55 % of pregnant women , obtaining therapeutic response in 45 % and failure in 17%. CONCLUSION : It was possible to improve after IEC intervention practice conscious consumption of 97 % iron . Regular monitoring and individual counseling transmitted permanent and appropriately were momentous .